The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.jaci.2009.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Activin and transforming growth factor-β signaling pathways are activated after allergen challenge in mild asthma

Abstract: Background-Both transforming growth factor (TGF)-β 1 and activin-A have been implicated in airway remodelling in asthma but the modulation of their specific signalling pathways after disease activation remains undefined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 33 publications
(48 reference statements)
5
75
2
1
Order By: Relevance
“…By contrast, certain studies point to proinflammatory effects of activin-A as shown by enhanced survival during systemic administration of follistatin following a lethal dose of LPS in vivo (8). Moreover, increased TNF-α and IL-1β release was observed upon stimulation of rat macrophages with activin-A in vitro (42). We believe that the discordance between the results presented in the latter study and ours may be due to the differences in the experimental set up employed (i.e., distinct species and cell types, stimulation protocol, and time point of Articles Petrakou et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, certain studies point to proinflammatory effects of activin-A as shown by enhanced survival during systemic administration of follistatin following a lethal dose of LPS in vivo (8). Moreover, increased TNF-α and IL-1β release was observed upon stimulation of rat macrophages with activin-A in vitro (42). We believe that the discordance between the results presented in the latter study and ours may be due to the differences in the experimental set up employed (i.e., distinct species and cell types, stimulation protocol, and time point of Articles Petrakou et al…”
Section: Discussionmentioning
confidence: 99%
“…The optimal doses of LPS, PHA, and r-activin-A were determined by dose-response studies (data not shown). A similar dose (50 ng/ml) of activin-A has been used in several studies for the examination of responses mediated by immune cells (35,41,42).…”
Section: In Vitro Stimulation Of Neonatal Peripheral Blood Leukocytesmentioning
confidence: 99%
“…Our previous studies, using an ovalbumin-induced mouse model of allergic airway inflammation, have revealed that activin-A protects against experimental asthma partly through the generation of Foxp3 − IL-10 + Treg cells (18). Moreover, we and others have shown that activin-A and its signaling components are induced in T cells infiltrating the lungs of asthmatics and become further up-regulated following in vivo inhalational allergen challenge (19,20). Still, the effects of activin-A on the generation of human Treg cells suppressive against allergic responses, and the molecular mechanisms involved, remain unexplored.…”
mentioning
confidence: 93%
“…In fact, activin A has been involved in different clinical inflammatory conditions such as rheumatoid arthritis, inflammatory bowel disease, allergic airway inflammation and clinical sepsis condition. [18][19][20][21][22] This review examines the recent findings about the role of activin signaling on immune cells, including the crosstalk with the Toll-like receptor (TLR) pathway, the impact in hematopoiesis and lymphocyte development, the effects on dendritic cell (DC) maturation, its emergence as a novel T helper cell type 2 (Th2) cytokine and its recent role in the induction of regulatory T-cell subsets. Collectively, these data support the role of activins/inhibins as key orchestrators of the immune system in homeostasis and inflammation.…”
mentioning
confidence: 99%